A Survey of Somatic Mutations in 41 Genes in a Cohort of T-Cell Lymphomas Identifies Frequent Mutations in Genes Involved in Epigenetic Modification. Issue 6 (July 2019) - Fernandez-Pol, Sebastian; Ma, Lisa; Joshi, Rohan P.; Arber, Daniel A.
Abstract : Here, we utilize a high throughput sequencing panel that covers several genes known to be recurrently mutated in certain T-cell lymphoma subtypes as well as genes frequently mutated in other hematolymphoid malignancies, including myeloid neoplasms. This panel was applied to formalin-fixed, paraffin-embedded tissue from 84 biopsies from 78 patients selected for this study. The biopsies included ones a with a diagnosis of T-cell lymphoma (n=79), including peripheral T-cell lymphoma not otherwise specified (PTCL-NOS; n=26) and angioimmunoblastic T-cell lymphoma (AITL; n=13), as well as 5 cases of atypical T-cell proliferations. KMT2C and KMT2D, which code for proteins involved in histone modifications, were the 2 most frequently mutated genes in our cohort and were altered across a range T-cell lymphomas. Mutations in TET2 and DNMT3A, which are involved in regulating DNA methylation, were also found in a variety of T-cell lymphoma categories. The RHOA G17V mutation that is frequently found in AITL was identified 5 of 13 (40%) cases of AITL and in 3 of 26 (12%) cases of PTCL-NOS, but not in biopsies involved by other T-cell proliferations. Our study adds to the already significant evidence from other investigators that, among T-cell lymphomas, the RHOA G17V variant is specific for AITL and PTCL-NOS. In contrast, variants in epigenetic modifier genes do not appear to be particularly specific for T-cell lymphoma subcategories evaluated in our study. Abstract : Supplemental Digital Content is available in the text.